Extreme value analysis of meteorological parameters observed during the period 1994–2022 at Kakrapar Gujarat site - D. P. Nankar; Akhaya Kumar Patra; I. V. Saradhi; A. Vinod Kumar (Radiation Protection and Environment)
Extreme meteorological parameters plays an important role, for the selection of any civil structure at nuclear site or to design important nuclear structures to withstand design basis values of meteorological extremes that are likely to occur during the lifetime of these structures. An attempt was made to study the extreme value analysis of meteorological parameters observed during the period 1994 to 2022 at Kakrapar Gujarat Site. Meteorological parameters such as extreme rainfall (mm) (yearly, monthly and daily), extreme surface ambient temperature (°C), minimum relative humidity (%), extreme atmospheric pressure (mbar) and extreme hourly wind speed (km.h-1) for two levels of measurement (10m and 30m height) are evaluated and described in this paper. The maximum and the minimum rainfall in a year was found to be 2278 mm and 772 mm, respectively. The maximum and minimum ambient temperature and atmospheric pressure was 44.6 °C, 2.2 °C and 1023 mbar and 987 mbar, respectively. The maximum hourly wind speed at 10 m and 30 m height was found to be 42.5 km.h-1 and 58.3 km.h-1, respectively. The extreme value analysis reveals that the variables for maximum annual rainfall, maximum ambient temperature, maximum atmospheric pressure, maximum hourly wind speed at 10m and at 30m height obey Fisher-Tippette type I distribution, whereas minimum annual rainfall, maximum monthly rainfall, maximum daily rainfall, minimum ambient temperature, minimum relative humidity, and minimum atmospheric pressure obey Fisher-Tippette type II distribution. The design basis values corresponding to return periods of 50, 100, 200 and 500 years are derived and also reported in this paper.